Warrior Burial from “Vysokaya Mogila – Studenikin Mar” Necropolis: New Finds of Defensive Armor of the Southern Urals Early Nomads - Sergey V. Sirotin; Konstantin S. Okorokov; Daria S. Bogachuk (Нижневолжский археологический вестник)
The article publishes a warrior burial from the Southern Urals. In the kurgan with specific features of the South Ural nomads’ elite burial rite, a central dromos with an individual burial of a nomadic military nobility representative was studied. In the burial, rich accompanying inventory was found which included elements of weapons, a bronze cauldron and a bronze ladle (bailer). The elements of the defenstive armor are of a particular research interest. These are fragments of iron laminar armor and a bronze scaly helmet with an iron laminar backplate. A scaly bronze helmet was found for the first time in the burial complexes of the South Ural nomads. Some of the items from the accompanying inventory in the burial have analogies not only in the complexes of the Filippovka circle in the South Urals, but also in the Scythian burials of the Dnieper region, the Middle and Lower Don, and the North Caucasus. A sacrificial complex in the area around the kurgan with elements of horse equipment is an interesting find. Some of the items from it have no analogues in the Southern Urals and are associated by their origin with the Scythian and Meotian complexes of the Dnieper, Don and Northern Caucasus. Based on the nature of the burial rite and the inventory, the studied complex dates back to the last third of the 4th – early 3rd centuries BC.